APLIKASI PENGHITUNG ZAKAT BERBASIS ANDROID (Information Technology and Telematics, 2014)
Muslims need to know the information about the charity well in its calculations or time to give zakat. Utilization of mobile phones as a companion device in performing daily activities is very familiar to everyone. This is because the number of mobile phones already have the functionality and capability beyond just basic functions. Android as an operating system that can dianamkan on device mobile phones have the ability to be able to install the applications needed by the user. At this writing zakat calculation application is developed, it is expected to Muslims who use the mobile phones based off the Android operating system can be aided to calculate zakat complicated and complex to be more accessible, effective and efficient. The end result of this research is based android application zakat counters can be used to calculate the amount of zakat that should be removed and the limit of the nisab of zakat agriculture, gold and silver alms, charity and zakat profession RikazKeywords – Zakat, Android, Prototype, Java